Diskursus Kerukunan Sosial Masyarakat Melalui Analisis Afeksi Hasil Pemilihan Umum 2024 Menggunakan Media Sosial X Dan Instagram - Bagus Setiawan; Alfiaturrohmah Alfiaturrohmah; Alifah Ilyana; Aprilia Yola Azhari; Debby Rofi’ah; Dewi Sophia Ariani; Moh. Afini Maulaya; Muhammad Ibadurrahman; Eprinda Nurro’in Habibah; Kharisma Yogi Febriantika; Nabella Zubaida’ Izzatur R; Andromeda Putri Herastita A; Da’i Syahrizal (Badan Penerbit STIEPARI Press, 2024)
This study aims to analyze the discourse on social harmony in society after the 2024 General Election through social media X and Instagram. In the contemporary context, social media has become a major platform for sharing opinions, views and emotions related to political events. This analysis uses a qualitative approach by utilizing sentiment analysis techniques to understand the affection contained in posts, comments and user responses. This research focuses on identifying affective patterns that emerge and how these patterns influence social harmony in society. It is hoped that the results of this research will provide insight into post-election social dynamics and the importance of social media in shaping public narratives regarding social harmony.